Genetic Analysis of Heterosis for Yield Influencing Traits in Brassica juncea Using a Doubled Haploid Population and Its Backcross Progenies - Aakanksha,; Yadava, Satish Kumar; Yadav, Bal Govind; Gupta, Vibha; Mukhopadhyay, Arundhati; Pental, Deepak; Pradhan, Akshay K. (Frontiers in Plant Science, 2021)
The exploitation of heterosis through hybrid breeding is one of the major breeding objectives for productivity increase in crop plants. This research analyses the genetic basis of heterosis in Brassica juncea by using a doubled haploid (DH) mapping population derived from F1 between two heterotic inbred parents, one belonging to the Indian and the other belonging to east European gene pool, and their two corresponding sets of backcross hybrids. An Illumina Infinium Brassica 90K SNP array based genetic map was used to identify yield influencing quantitative trait loci (QTL) related to plant architecture, flowering, silique and seed related traits using five different data sets from multiple trials, allowing the estimation of additive and dominance effects as well as digenic epistatic interactions. In total, 695 additive QTL were detected for the 14 traits in the three trials using five data sets, with over-dominance observed to be the predominant type of effect in determining the expression of heterotic QTL. The results indicated that the design in the present study was efficient for identifying common QTL across multiple trials and populations which constitute a valuable resource for MAS and further research. In addition, a total of 637 epistatic loci were identified, and it was concluded that epistasis among loci without detectable main effects plays an important role in controlling heterosis in yield of B. juncea.